Fat free mass and obesity in relation to educational level - Rissanen Harri; Knekt Paul; Männistö Satu; Lahti-Koski Marjaana; Seppänen-Nuijten Elina; Aromaa Arpo; Heliövaara Markku (BMC, 2009)
Abstract Background The aim of the study was to describe the body composition of Finnish adults, especially by education, and to investigate whether fat-free mass (FFM) can explain educational gradients relating to body mass index (BMI) and waist-to-hip ratio (WHR). Methods Data for this cross-sectional study were based on data collected in 2000-2001 for the Health 2000 Survey. Of the nationally representative sample of 8,028 Finnish men and women aged 30 years and older, 6,300 (78.5%) were included in the study. Body composition measurements were carried out in the health examination, where FFM was assessed with eight-polar bioelectrical impedance analysis. Questions on education were included in the health interview. Results The mean FFM varied by education in older (≥ 65 y.) men only. In the middle-aged group (30-64 y.), highly educated men were less likely to belong to the lowest quintile of FFM (OR 0.67, 95%CI 0.48-0.93) compared with the least educated subjects. The level of education was inversely associated with the prevalence of high BMI and WHR in middle-aged men. In women, the respective associations were found both in middle-aged women and their older counterparts. Adjustment for FFM slightly strengthened the associations of education with BMI and WHR. Conclusions The association between education and FFM is weak. Educational gradients of high BMI and high WHR cannot be explained by FFM.